2023
DOI: 10.1021/acsanm.3c02162
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of miR-34a-5p by Folic Acid-Modified β-Cyclodextrin-Grafted Polyethylenimine Copolymer Nanocarriers to Resist KSHV

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) infection can cause a range of malignancies. The use of microRNA (miRNA) to combat viruses and inhibit tumor development has received increasing attention. However, it is difficult for free miRNA to enter into cells directly and to degrade easily. Therefore, the miRNA therapy alone often fails to achieve the expected effect. The selection of an appropriate delivery system for effective miRNA delivery and anti-KSHV is rarely considered. In this study, a β-cyclodext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that modifying miRNA with polymeric nanocarriers can help prevent their degradation outside the cell and facilitate their entry into target cells, thereby influencing the expression of target genes, which plays a role in gene therapy. 34 Herein, N3-PEG-PLys (Fig. S1, ESI†) was used as a polymer to prepare the miRNA-loaded PLL micelles.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that modifying miRNA with polymeric nanocarriers can help prevent their degradation outside the cell and facilitate their entry into target cells, thereby influencing the expression of target genes, which plays a role in gene therapy. 34 Herein, N3-PEG-PLys (Fig. S1, ESI†) was used as a polymer to prepare the miRNA-loaded PLL micelles.…”
Section: Resultsmentioning
confidence: 99%
“…In order to detect the protective effect of the carrier on miR-34a-5p (1 μg/per well), free miR-34a-5p, LA-PEI/miR-34a-5p, and LA-PEI-PBA/miR-34a-5p were mixed with 50% FBS (Fangling et al, 2023) or RNase A solution (10 μg/mL) at room temperature for 1 h, and then agarose gel electrophoresis was performed (the same conditions as in 2.5).…”
Section: Protective Assaymentioning
confidence: 99%
“…The primers are shown in Supplementary Table S1. Then real-time PCR was used to amplify the target fragment and the reaction conditions described in our previous study (Fangling et al, 2023).…”
Section: Rna Extraction and Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation